Metagenomics analysis reveals presence of the Merida-like virus in Georgia - Potter-Birriel, Jennifer M.; Pollio, Adam R.; Knott, Brian D.; Chunashvili, Tamar; Fung, Christian K.; Conte, Matthew A.; Reinbold-Wasson, Drew D.; Hang, Jun (Frontiers in Microbiology, 2023)
Arbovirus surveillance is fundamental for the discovery of novel viruses and prevention of febrile vector-borne illnesses. Vector-borne pathogens can rapidly expand and adapt in new geographic and environmental conditions. In this study, metagenomic surveillance was conducted to identify novel viruses in the Country of Georgia. A total of 521 mosquitoes were captured near a military training facility and pooled from species Culex pipiens (Linnaeus) (87%) and Aedes albopictus (Skuse) (13%). We decided to further analyze the Culex pipiens mosquitoes, due to the more extensive number of samples collected. Our approach was to utilize an unbiased total RNA-seq for pathogen discovery in order to explore the mosquito virome. The viral reads from this analysis were mostly aligned to Insect-specific viruses from two main families, the Iflaviridae; a positivestranded RNA virus and the Rhabdoviridae; a negative-and single-stranded RNA virus. Our pathogen discovery analysis revealed viral reads aligning to the Merida-like virus Turkey (MERDLVT) strain among the Rhabdoviridae. To further validate this result, we conducted a BLAST sequence comparison analysis of our samples with the MERDLVT strain. Our positive samples aligned to the MERDLVT strain with 96-100% sequence identity and 99.7-100% sequence coverage. A bootstrapped maximum-likelihood phylogenetic tree was used to evaluate the evolutionary relationships among these positive pooled specimens with the (MERDLVT) strain. The Georgia samples clustered most closely with two strains from Turkey, the Merida-like virus KE-2017a isolate 139-1-21 and the Merida-like virus Turkey isolate P431. Collectively, these results show the presence of the MERDLVT strain in Georgia.